Experimental Investigation of Machining Characteristics of Titanium Alloy (Ti-6Al-4V) by using EDM Process - Chib, Sunny Singh (My University, 2015)
With the invention of super alloys such as titanium based super alloys, nickel based super alloys, carbides, stainless steels, hastelloy, nitralloy, etc., increases the need of non-traditional manufacturing processes. These materials are so hard and tough that they can-not be machined by conventional machining processes. Such materials finds a large variety of applications, especially titanium based super alloys where high strength to weight ratio and hardness is required. The materials which fulfill the modern industry’s demand are very difficult to machine. Non conventional machining methods have been developed to control the machining problem. Electrical discharge machining (EDM) is the most commonly used method among the new machining methods. It is widely used because of its capability to process difficult to machine materials and intricate shapes. It can modify the surface properties such as roughness and hardness of different materials by changing the electrode material and also by mixing different powders in the dielectric. Powder mixed electric discharge machining is the latest innovation for increasing the machining capabilities. Ti-6Al-4V is the material with unique properties like high strength to weight ratio, corrosion resistance, high temperature strength, weld and fabricability makes it most attractive material. Due to its applicability in different industrial application like in aerospace, marine etc., selected for thesis purpose along with copper as electrode and kerosene as dielectric. As Ti-6Al-4V has low electrical conductivity so graphite and copper powders has been mixed with dielectric fluid. Three factors at three levels each i.e. peak current, pulse-on time and different powder mixed dielectric has been choosen to investigate the effect of powder on output responses. The output responses are material removal rate (MRR), tool wear rate (TWR), surface roughness (Ra) and micro-hardness. In this thesis work, Taguchi method has been applied to design the experiments by adopting an appropriate orthogonal array, so that study can be conducted with minimum possible number of experiments. The experiments have been performed as per as L27orthogonal array. ANOVA is the main statistical tool used to analyze results both analytically as well as graphically, by indicating the percentage contribution of each factors on all output responses. From the experimental results it is found that material removal rate, surface roughness and micro-hardness increases with the addition of powders. Material removal rate, tool wear rate, surface roughness and micro hardness were also optimized in the study and the optimal value of each of the above response was calculated using their signal to ratio values. Grey relation analysis has been used to unearth the best result for different outcomes of the EDM process.
M.E. (Production Engineering)
Keywords: EDM; Taguchi Design; PMEDM; Orthogonal Array; Grey Relation Analysis; Titanium Alloy; Production Engineering; Mechanical Engineering